ANTESEDEN DARI NIAT KUNJUNGAN ULANG PADA PASAR KULINER MALAM STUDI PADA PASAR KULINER DUTA MAS DI JAKARTA BARAT - Inggrid Indira Zeta,; Valencia Cherish,; Nonot Yuliantoro, (Journal of Innovation Research and Knowledge, 2024)
This study aimed to explore the factors influencing the intention to revisit Duta Mas Night Culinary, West Jakarta. With a theoretical model approach that connects two main variables, namely Food Neophilia and Electronic Word of Mouth (eWOM) through Attitude towards food in night culinary, this study tests the relationship hypothesis between these variables. The method in this study is quantitative by conducting a survey. Data was collected using an online questionnaire instrument. The target population studied at Duta Mas Night Culinary, West Jakarta was aged 20 years and over to more than 35 years who lived in Jakarta, Bogor, Depok, Tangerang, Bekasi, and non-Jabodetabek. Valid respondents were 275 (two hundred and seventy-five) respondents from 395 (three hundred and ninety-five) samples. The technique of data collection in this study was purposive sampling. The measuring instrument used was PLS-Sem to obtain the results of the data analysis. The results obtained from this study are that Food Neophilia has a positive and significant influence on Attitude towards food (H1), while eWOM also has a direct positive and significant influence on Attitude towards food (H2) at Duta Mas Night Culinary, West Jakarta and Attitude towards food has a direct influence on Intention to Revisit (H3). On the other hand, Attitude toward food has a direct influence on Intention to Revisit (H4) at Duta Mas Night Culinary, West Jakarta